Pengaruh Word of mouth dan Store Atmsophere terhadap Kepuasan dan dampaknya terhadap Loyalitas (Studi pada Pelanggan Antariksa Kopi Semarang) - Islakhul khoir; Endang Tjahjaningsih (Universitas Batanghari Jambi, 2023)
Coffe shop is a place that is not just a place to sell and enjoy coffee, besides coffee shop is also used for some specific needs, either relax, gather, discuss, do tasks, place photos and so forth. This study aims to determine the effect of word of mouth and store atmosphere on satisfaction and its impact on loyalty at Angkasa Kopi Semarang. Research conducted in Antariksa Kopi Semarang is a type of quantitative research. The data source used using a questionnaire via google form to 100 respondents with purposive sampling methodology. Hypothesis testing using multiple linear regression test using statistical data processing based on SPSS 26. The results showed that the variable word of mouth has no effect on satisfaction,store atmosphere has a positive and significant effect on satisfaction, and satisfaction has a positive and significant effect on loyalty.